Comparison the Effectiveness of Positive Self-Talk Training and Self-Control Training Methods on Self-Efficacy Beliefs of High School Girl Students - Esmaeil Sadipour; Zahra Ghalami; Hasan Asadzadeh (Iranian Association of Health Education and Health Promotion, 2019)
Background and Objective: The review of literature suggests self-talk and self-control as effective methods for improving mental health and achievement of goals. Considering the importance of improving the level of self-efficacy of students, this study aimed to compare the effectiveness of positive self-talk and self-control training on self-efficacy of 10th high school female students. Methods: The present study is a semi-experimental design with pre-test post-test design with experimental and control groups. The research population is female students who study in 10th grade of the empirical sciences of public schools in Tehran's 2nd district in 2017-2018. The sample size was 60 students who were selected by simple random and simple cluster sampling method, and they were randomly assigned into three groups of 20 subjects, two experimental groups (one self-talk and one self-control training group) and one control group. Each of the experimental groups was trained for 10 weeks. To measure self-efficacy, the general self-efficacy questionnaire of Sherer et al. (1982) was used. Data analysis was performed using SPSS 21 and one-way covariance analysis. Results: The results indicated that positive self-talk and self-control training were effective on self-efficacy of students. Also, there is difference between effectiveness of these two methods on self-efficacy, and self-control training had greater effect on increasing self-efficacy (P<0/001). Conclusion: Regarding the effectiveness of positive self-talk and self-control training on general self-efficacy of students, it is desirable to conduct training courses on positive self-talk and emotional self-control in schools by counselors and therapists.